Risk Factors Associated With Young-Onset Colorectal Adenomas and Cancer: A Systematic Review and Meta-Analysis of Observational Research. (2nd December 2020) - Breau, Genevieve; Ellis, Ursula
The risk of young-onset colorectal adenomas and cancer (yCRAC) in adults less than 50 years of age is increasing. We conducted a systematic review and meta-analysis of epidemiologic studies to identify lifestyle and clinical risk factors associated with yCRAC risk. We searched Medline, EMBASE, and Cochrane Database of Systematic Reviews for studies which: used an epidemiologic study design, involved individuals with yCRAC, evaluated at least 1 lifestyle or clinical factor, and applied multivariable regression approaches. We critically appraised the quality of included studies and calculated pooled measures of association (e.g. odds ratio [OR]) and 95% confidence intervals (CI) using random-effects models. We identified 499 articles in our search with 9 included in a narrative synthesis and 6 included in a meta-analysis. We found in the pooled analysis that smoking and alcohol consumption were lifestyle factors associated with yCRAC, as were clinical factors including obesity elevated blood glucose, elevated blood pressure, and elevated triglycerides. We identified lifestyle and clinical risk factors associated with risk of yCRAC, which have potential implications for informing preventive efforts and modifying screening to target at-risk populations.